Deficient DNASE1L3 facilitates neutrophil extracellular traps‐induced invasion via cyclic GMP‐AMP synthase and the non‐canonical NF‐κB pathway in diabetic hepatocellular carcinoma. Issue 4 (20th April 2022) - Li, Na; Zheng, Xue; Chen, Mianrong; Huang, Li; Chen, Li; Huo, Rui; Li, Xiaotong; Huang, Yucan; Sun, Mingwen; Mai, Suiqing; Wu, Zhuoyi; Zhang, Hui; et al.
Abstract: Objective: Diabetic hepatocellular carcinoma (HCC) patients have high mortality and metastasis rates. Diabetic conditions promote neutrophil extracellular traps (NETs) generation, which mediates HCC metastasis and invasion. However, whether and how diabetes‐induced NETs trigger HCC invasion is largely unknown. Here, we aimed to observe the effects of diabetes‐induced NETs on HCC invasion and investigate mechanisms relevant to a DNA sensor cyclic GMP‐AMP synthase (cGAS). Methods: Serum from diabetic patients and healthy individuals was collected. Human neutrophil‐derived NETs were isolated for stimulating HCC cell invasion. Data from the SEER and TCGA databases were used for bioinformatics analysis. In HCC cells and allograft models, NETs‐triggered invasion was observed. Results: Diabetic HCC patients had poorer survival than non‐diabetic ones. Either diabetic serum or extracted NETs caused HCC invasion. Induction of diabetes or NETosis elicited HCC allograft invasion in nude mice. HCC cell invasion was attenuated by the treatment with DNase1. In TCGA_LIHC, an extracellular DNase DNASE1L3 was downregulated in tumor tissues, while function terms (the endocytic vesicle membrane, the NF‐κB pathway and extracellular matrix disassembly) were enriched. DNASE1L3 knockdown in LO2 hepatocytes or H22 cell‐derived allografts facilitated HCC invasion in NETotic or diabetic nude mice. Moreover, exposure of HCC cells to NETs upregulated cGAS and the non‐canonical NF‐κB pathway and induced expression of metastasis genes ( MMP9 and SPP1 ). Both cGAS inhibitor and NF‐κB RELB knockdown diminished HCC invasion caused by NETs DNA. Also, cGAS inhibitor was able to retard translocation of NF‐κB RELB. Conclusion: Defective DNASE1L3 aggravates NETs DNA‐triggered HCC invasion on diabetic conditions via cGAS and the non‐canonical NF‐κB pathway. Abstract : In this study, we found that diabetes‐induced NETs release was significant for hepatocellular carcinoma invasion. Non‐canonical NF‐κB pathway‐mediated MMP9 and SPP1 expression was involved in this process. DNA sensor cyclic GMP‐AMP synthase was a key mediator for activating the above pathway.